Respon Pertumbuhan dan Hasil Beberapa Varietas Tanaman Sawi Hijau (Brassica juncea L.) terhadap Pemberian Pupuk Organik Cair Air Cucian Beras - Dwi K., Krismunandar Asep; Santosa, I Gusti Ngurah; Astawa, I Nyoman Gede (Agrotrop : Journal on Agriculture Science, 2023)
Growth and Yield Response of Several Varieties of Caisim ( Brassica juncea L.) to Application of Liquid Organic Fertilizer with Rice Washing Water. The study was conducted in the Green House of the Center for Supervision and Certification of Food Crops and Horticulture Seeds, Bali Province and in Agronomy and Horticulture Laboratory, Udayana University. This study was started from March 2021 to May 2021. The study aims to obtain the best variety and the accurate concentration of liquid organic fertilizer on several caisim varieties and to determine treatment interactions. The study was conducted using a factorial Completed Randomized Block Design with two factors. The first factor uses the caisim variety which consists of three varieties, namely SA 764, shinta and tosakan variety. The second factor is concentration of liquid organic fertilizer which consists of four levels, namely Control, 10, 20, and 30 ml/L water. Each treatment was repeated three times. The results showed that the interaction beetwen the caisim variety and the concentration of liquid organic fertilizer showed a very significant differences in leaf number. The caisim variety individually showed significant differences in plant dry weight and very significant differences in plant height and plant fresh height. The treatment of liquid organic fertilizer concentration showed very significant on plant height, leaf area, plant fresh weight and plant dry weight.